Plato and Xenophon : comparative studies - Danzig, Gabriel, 1961- (Mnemosyne, Supplements, 2018)
Plato and Xenophon are the two students of Socrates whose works have come down to us in their entirety. Their works have been studied by countless scholars over the generations; but rarely have they been brought into direct contact, outside of their use in relation to the Socratic problem. This volume changes that, by offering a collection of articles containing comparative analyses of almost the entire range of Plato's and Xenophon's writings, approaching them from literary, philosophical and historical perspectives.